Bibliografi Beranotasi Tugas Akhir Jurusan Sistem Produksi Industri dan Jurusan Teknik Kimia Akademi Teknologi Industri Padang (ATIP) Tahun 2012 - 2013 - Yanto, Syofi; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2014)
This article aims to describe the annotated bibliography as a means of making information searchers search for information on Student Final Program indusri Production Systems and Chemical Engineering, College of Industrial Technology Padang (ATIP) 2012-2013 the existing collection of scientific works in the library that comes with the ATIP inclusion of annotations. Inclusion of annotations in the annotated bibliography aims to help information seekers get a picture, illustration literature required contents. Advantages that are obtained seekers can find out information about the final project. The results of the study stated that the determination of the stage of making a bibliography is a bibliography of titles, in this case to consider is about the availability of a collection, use the collection to the user and what information is most needed by the user or pemustaka. The collection of library materials relating to the collection of things that have successfully traced recorded information about the author, Legal information, physical description or collation as well as additional information or annotation. Selection of library materials, the selection is intended that the articles collected in accordance with the specified topic grouping or classification. Keywords: Bibliography, Annotated, Industrial Production Systems